Structural and enzymatic characterization of the phosphotriesterase OPHC2 from Pseudomonas pseudoalcaligenes. - Guillaume Gotthard (Public Library of Science (PLoS), 2013)
Background Organophosphates (OPs) are neurotoxic compounds for which current methods of elimination are unsatisfactory; thus bio-remediation is considered as a promising alternative. Here we provide the structural and enzymatic characterization of the recently identified enzyme isolated from Pseudomonas pseudoalcaligenes dubbed OPHC2. OPHC2 belongs to the metallo-β-lactamase superfamily and exhibits an unusual thermal resistance and some OP degrading abilities. Principal findings The X-ray structure of OPHC2 has been solved at 2.1 Å resolution. The enzyme is roughly globular exhibiting a αβ/βα topology typical of the metallo-β-lactamase superfamily. Several structural determinants, such as an extended dimerization surface and an intramolecular disulfide bridge, common features in thermostable enzymes, are consistent with its high Tm (97.8°C). Additionally, we provide the enzymatic characterization of OPHC2 against a wide range of OPs, esters and lactones. Significance OPHC2 possesses a broad substrate activity spectrum, since it hydrolyzes various phosphotriesters, esters, and a lactone. Because of its organophosphorus hydrolase activity, and given its intrinsic thermostability, OPHC2 is an interesting candidate for the development of an OPs bio-decontaminant. Its X-ray structure shed light on its active site, and provides key information for the understanding of the substrate binding mode and catalysis.